Hydrazone comprising compounds as promising anti-infective agents: chemistry and structure-property relationship. (December 2020) - Sharma, P.C.; Sharma, D.; Sharma, A.; Saini, N.; Goyal, R.; Ola, M.; Chawla, R.; Thakur, V.K.
Abstract: Despite the adverse effects of microbial hazards on public health, major pharmaceutical firms have left the field of anti-infective development and a dramatic reduction in the number of researcher's intricated in the quest for new specific anti-infective leads. In the non-existence of an efficient forum for antibiotics development and over usage in human beings and animals, bacteria have demoralized this potential by gradually establishing the resistance toward most of the antibiotics used. Thus, the production of novel and successful anti-infective drugs is urgently required to combat this resistance. Hydrazones and hydrazides have mounted as a key-skeleton for the development of active drugs, due to their important biological and pharmacological profiles. Hydrazones are being manufactured as medicines by various investigators to fight against the ailments with maximal effects and minimal toxicity. This paper focuses on the outline of the literature results of recent years, incorporating the work on the anti-infective profile of hydrazone analogues. This review may also act as an excellent basis for the development of new derivatives of hydrazone as potential anti-infective mediators. Graphical abstract: Image 1 Highlights: Potential of hydrazone derivatives for development of newer pharmacologically active anti-infective agents. SAR study of hydrazone based analogues Concise description of nanocarriers as efficient anti-infective agents. A brief discussion on patents filed/granted on hydrazone derivatives as anti-infective agents.